PENGARUH ZEOLIT PADA MEDIA TANAM TERHADAP PENYERAPAN POC SECRA HIDROPONIK SISTEM IRIGASI TETES Brassica juncea L. - Layyina, Naviri; Muspiah, Aida; Julisaniah, Nur Indah (University of Mataram, 2022)
Hydroponic drip irrigation technique is a system of giving water by dripping directly on the area around plant roots. Nutrients commonly used in hydroponic systems are AB Mix which is made from synthetic chemicals. It is expected that these nutrients can be replace with liquid organic fertilizers (POC), but the use of POCs has resulted in poor plant growth due to the lack of plant absorption of POCs. Liquid organic fertilizer absorption can be increased by using planting media with high CEC (cation exchange capacity) such as zeolites. This study was conducted to determine the effect of zeolite on POC absorption on the growth of mustard greens (Brassica juncea L.) grown hydroponically with drip irrigation technique and to determine the optimum concentration. The study used the RAL method (Completely Randomized Design) with a ratio of zeolite and husk charcoal, namely 100% husk charcoal as control (P0), zeolite 15% (P1), 30% (P2), and 45% (P3). Twenty plants used in each treatment. The results showed that P3 had the most optimal growth compared to other treatments, both in terms of the average leaf area of ​​162.88 cm2, as well as fresh weight of 17.24 grams, and dry weight of 1.08 grams.